Generation and energy exchange of charge states in organic molecular crystoline scintillators - Tarasenko, O.A. (Functional Materials, 2012)
This paper discusses the physical processes that determine the aspects of generation and energy exchange of charge states, which arise in molecular organic media by an action of ionizing radiations of different types. The semi-empirical description of the primary processes of energy exchange in the track of ionizing particles is analyzed. This description takes into account the primary influence of the polarization processes on the charge states energy exchange and quenching processes. The process of quenching is determined by the very fast initial recombination of the molecular polaron pair. This process, at least, is an order of magnitude faster than the process of diffusion expanding of the track, and its efficiency increases with the density of the recombining pairs. The analysis is based on the results of the measurements of the light yield of stilbene and p-terphenyl scintillation detectors as the function of energy for the cases of alpha-, neutron- and gamma excitations. We have studied structurally perfect organic single crystals, hot-pressed polycrystals and composite scintillators. The obtained results testify about the primary influence of the type of ionizing radiation in comparison with the influence of the matter structure.This paper discusses the physical processes that determine the aspects of generation and energy exchange of charge states, which arise in molecular organic media by an action of ionizing radiations. The primary energy loss of a charged ionizing particle in the regions of high density of excitation and the possible causes of this effect are considered. У роботі обговорюються фізичні процеси, що визначають особливості генерації та розміну енергії зарядових станів, які виникають у молекулярних органічних середовищах під дією іонізуючих випромінювань різних типів. Аналізується напівемпіричний опис процесів первинного розміну енергії у треку іонізуючої частинки. Даний опис ураховує визначальний вплив поляризаційних процесів на розмін енергії зарядових станів і процеси гасіння. Процес первинного гасіння визначається дуже швидкою рекомбінацією молеку-лярно-поляронної пари. Цей процес як мінімум на порядок швидше процесу дифузійного розширення треку, а його ефективність росте зі збільшенням густини пар, які ре-комбінують. Аналіз грунтується на результатах вимірів величини світлового виходу органічних сцинтиляційних детекторів на основі стильбену та л-терфенілу як функції енергії при альфа-, нейтронному- та гамма-збудженні. Досліджувалися структурно досконалі органічні монокристали, полікристали, отримані методом гарячого пресування, композиційні сцинтилятори. Отримані результати свідчать про визначальний вплив типу іонізуючого випромінювання у порівнянні із впливом структури речовини на процеси, які обговорюються. В работе обсуждаются физические процессы, определяющие особенности генерации и размена энергии зарядовых состояний, возникающих в молекулярных органических средах под действием ионизирующих излучений различных типов. Анализируется полуэмпирическое описание процессов первичного размена энергии в треке ионизирующей частицы. Данное описание учитывает определяющее влияние поляризационных процессов на размен энергии зарядовых состояний и процессы тушения. Процесс первичного тушения определяется очень быстрой рекомбинацией молекулярно-поляронной пары. Этот процесс как минимум на порядок быстрее процесса диффузионого расширения трека, а его эффективность растет с ростом плотности рекомбинирующих пар. Анализ основывается на результатах измерений величины светового выхода органических сцинтилляционных детекторов на основе стильбена и n-терфенила как функции энергии при альфа-, нейтронном- и гамма-возбуждении. Исследовались структурно совершенные органические монокристаллы, поликристаллы, полученные методом горячего прессования, композиционные сцинтилляторы. Полученные результаты свидетельствуют в пользу определяющего влияния на изучаемые процессы типа ионизирующего излучения по сравнению с влиянием структуры вещества.